2022
DOI: 10.3389/fphar.2022.838688
|View full text |Cite
|
Sign up to set email alerts
|

Sivelestat Alleviates Atherosclerosis by Improving Intestinal Barrier Function and Reducing Endotoxemia

Abstract: Emerging evidence suggests that atherosclerosis, one of the leading phenotypes of cardiovascular diseases, is a chronic inflammatory disease. During the atherosclerotic process, immune cells play critical roles in vascular inflammation and plaque formation. Meanwhile, gastrointestinal disorder is considered a risk factor in mediating the atherosclerotic process. The present study aimed to utilize sivelestat, a selective inhibitor of neutrophil elastase, to investigate its pharmacological benefits on atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It is currently the only drug approved worldwide for the treatment of ALI/ARDS [20][21][22]. Recent studies have found that the powerful antiin ammatory ability of SV may also have a better inhibitory effect on the in ammatory response in other organs [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…It is currently the only drug approved worldwide for the treatment of ALI/ARDS [20][21][22]. Recent studies have found that the powerful antiin ammatory ability of SV may also have a better inhibitory effect on the in ammatory response in other organs [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of homeostasis in the intestine is associated with factors such as the intestinal mucosal barrier, the internal environment, and its metabolites, in which the structure of the microbiota changes successively under conditions in which intestinal homeostasis is disrupted, and the gut microbiota and its metabolites can influence the intestinal barrier at all levels [25] . The beneficial bacteria can inhibit pathogenic bacteria reproduction, which can maintain gut microbiota homeostasis by increasing tight junction (TJ) protein content, prompting epithelial cell proliferation and differentiation, and promoting mucus and anti-inflammatory factor production, leaving the intestinal barrier intact and the inflammation level stable, which is beneficial for reducing the risk of diseases such as as as and its risk factors [26] . From the analysis of gut microbiota, calycosin was identified as an increase the diversity and richness of gut microbiota in AS mice compared with HFD group.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the mechanism by which excessive neutrophils injure the gingival epithelial barrier is yet to be clarified. In addition, it was reported that NE inhibitor decreases endotoxemia by improving intestinal permeability and intestinal inflammatory response 33 ; however, the positive effect of NE inhibitor on periodontitis has rarely been reported. In this study, NE cleaved cell adhesion molecules and increased gingival epithelial cell monolayer permeability of periodontal pathogen in vitro.…”
Section: Discussionmentioning
confidence: 99%